The Effect of Using Two Stay-Two Stray Method Toward Students' Motivation in Learning English - Sari , Rina; Asriyanti, Asriyanti; Husain, Dahlia; Thayib Pido , Nur Wahidah (ELOQUENCE : Journal of Foreign Language, 2022)
Background: Two stay-two stray is one of the models of learning cooperative learning models based on group work where the teacher divides students into several groups, and each group of students will visit another group (two live two guests) to share knowledge and experience with other group students. Purpose: The aim of this study is to determine the effect of the use of the Two Stay Two Stray method on student motivation in learning English in class XI IPA.1 MAN 1 Kabupaten Gorontalo. Method: The methodology used in this study is a quantitative research method with One-Shot Case Study research design which is part of Pre-Experimental Design. Results and Discussion: The results showed that there was a significant influence in the use of the Two Stay Two Stray method on learning motivation in learning English. Conclusions and Implications: Based on the research data and description of the data that has been described, the researcher concludes that: The average student learning rate increases after learning by Two Stay Two Stray method, this is evidenced by the results of the assessment of the learning motivation questionnaire and Two Stay Two Stray method to 27 students as experimental classes, prove that there are 17 students classified as criteria very good and 24 students for Two Stay Two Stray method. The use of the Two Stay Two Stray method has proven effective in enhancing student learning motivation. This means that the method can be more widely implemented in classrooms to encourage higher student engagement and improve their learning outcomes. Teachers who adopt this method can expect increased motivation and active participation from most students